Studi komparatif kinerja keuangan daerah Kota Jambi dan Provinsi Jambi - Herlin, Faradilla; Syurya Hidayat, M. (Jurnal Paradigma Ekonomika, 2021)
The analysis carried out aims to perform a comparative analysis of the regional financial performance of Jambi City and Jambi Province. The analytical method used is the secondary data comparative analysis method. The analytical model used is an indicator of fiscal dependence, income generation capacity, an indicator of the proportion of capital expenditures, and an indicator of the contribution of the government sector. The analysis results conclude that overall, the regional financial performance of Jambi City is better than Jambi Province. Â